STUNTING PREVENTION BEHAVIOR IN EARLY MARRIAGE FAMILIES IN SUKAHAJI, BABAKAN CIPARAY - Salma, Aisha Syarifa; Pradytia, Wendy; Susilowati, Ellya; Rosilawati, Rosilawati (Indonesian Journal of Social Work, 2026)
Abstract Stunting is influenced by biological factors and broader social determinants, and families formed through early marriage face layered vulnerabilities that weaken household-level prevention. This study aimed to describe stunting prevention behaviors among early married families in Sukahaji Subdistrict, Babakan Ciparay District, Bandung City, using a three-level prevention framework. A qualitative descriptive study was conducted through in-depth interviews with five mothers who married before age 19, selected purposively, supported by key informants (community social workers and posyandu cadres), as well as observation and documentation; data were analyzed thematically. The findings indicate that primary prevention was fragile due to low literacy on stunting and pregnancy nutrition, incomplete understanding of health guidance, psychosocial barriers, and socioeconomic constraints that made pregnancy diets largely dependent on household food availability. Secondary prevention was reactive and relied on posyandu monitoring and cadre prompting, with responses focused on increasing food intake and providing milk, supported by PMT and DASHAT but not consistently grounded in comprehensive nutrition understanding. Tertiary prevention involved gradual behavior change following external guidance, yet sustained home-based rehabilitation was constrained by limited practical nutrition skills, economic barriers, and weak social support, and preventive outreach to adolescents to reduce early marriage was uneven. These findings highlight the central role of posyandu cadres as local connectors and the need to strengthen maternal health literacy, practical caregiving skills, and socioeconomic support to achieve sustainable household-level stunting prevention. Keywords: Stunting, Prevention Behavior, Early Marriage, Qualitative Study, Posyandu, Indonesia